ECTHR_COMMITTEE 38059/12 vom 9. Juli 2024 , AFFAIRE TUTAKBALA c. TÜRKİYE - Ecthr Committee (2024)
Radiation du rôle (Article 37-1 - Radiation du rôle;Article 37-1-b - Litige résolu;Article 37-1-c - Poursuite de l'examen non justifiée)